2020
DOI: 10.1002/adom.201901684
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Super Broadband NIR Ca2LuZr2Al3O12:Cr3+,Yb3+ Garnet Phosphor for pc‐LED Light Source toward NIR Spectroscopy Applications

Abstract: Super broadband near‐infrared (NIR) phosphor converted light‐emitting diodes (pc‐LEDs) are future light sources in NIR spectroscopy applications such as food testing. At present, a few blue LED excitable super broadband NIR phosphors (bandwidth > 300 nm) have been developed producing the NIR output powers below 26 mW at 100 mA input current after LED packaging. Here, an efficient super broadband NIR phosphor achieved by doping Yb3+ is reported in the NIR Ca2LuZr2Al3O12:Cr3+ (CLZA:Cr3+) garnet phosphor develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(77 citation statements)
references
References 41 publications
0
71
1
1
Order By: Relevance
“…Note that Yb 3+ infrared emission based on the Cr 3+ →Yb 3+ energy transfer has also been observed in other material systems 40 – 42 . For example, by co-doping Yb 3+ into Ca 2 LuZr 2 Al 3 O 12 :Cr 3+ phosphor and adjusting the Yb 3+ concentration, He et al achieved super broadband NIR luminescence with a large FWMH of 320 nm and a high absolute quantum yield of 77.2% 40 . Yao et al demonstrated that the NIR photoluminescence performance of LiScP 2 O 7 :Cr 3+ phosphor can be greatly improved after co-doping Yb 3+, 41 .…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Note that Yb 3+ infrared emission based on the Cr 3+ →Yb 3+ energy transfer has also been observed in other material systems 40 – 42 . For example, by co-doping Yb 3+ into Ca 2 LuZr 2 Al 3 O 12 :Cr 3+ phosphor and adjusting the Yb 3+ concentration, He et al achieved super broadband NIR luminescence with a large FWMH of 320 nm and a high absolute quantum yield of 77.2% 40 . Yao et al demonstrated that the NIR photoluminescence performance of LiScP 2 O 7 :Cr 3+ phosphor can be greatly improved after co-doping Yb 3+, 41 .…”
Section: Resultsmentioning
confidence: 58%
“…Nevertheless, the blue light absorption ability of Yb 3+ is significantly weak due to the absence of energy levels in the blue region, making it hard to achieve high-efficient SWIR luminescence by the use of readily available and high-power blue LED chips. Just recently, Yb 3+ has been co-doped into Cr 3+ -activated broadband NIR-emitting phosphors to broaden the spectral bandwidth and improve the NIR luminescence performance in view of the efficient Cr 3+ →Yb 3+ energy transfer under the excitation of blue LED 40 45 . However, with regard to this application, Cr 3+ emission and Yb 3+ emission usually appear simultaneously with comparable luminescence intensities in order to achieve super broadband NIR LED application, while the intense and dominant emission band over 940–1200 nm from Yb 3+ for SWIR LEDs and their practical applications have largely gone unnoticed.…”
Section: Introductionmentioning
confidence: 99%
“…and Yao et al. improved the luminous efficiency, thermal resistance, and FWHM of Ca 2 LuZr 2 Al 3 O 12 :Cr 3+ and LiScP 2 O 7 :Cr 3+ phosphors by Yb 3+ co-doping, respectively ( He et al, 2020 , Yao et al., 2020 ). However, the emission spectra of most NIR phosphors activated by Cr 3+ ions have a considerable part in the visible light range (650-780 nm), which has inferior permeability to biotissues compared with long-wavelength NIR light and will cause irritation to naked eyes.…”
Section: Introductionmentioning
confidence: 99%
“…[7] However, the emission of these Cr 3 + doped phosphors are not broad enough to fully cover the first NIR window (NIR-I, 650-950 nm), [8] and the FWHM can only reach around 200 nm even after optimization by co-doping Yb 3 + . [9] In addition, the preparation of phosphor containing Cr 3 + can be accompanied by the production of Cr 6 + , which is a substance with potential carcinogenic risk. [10] Therefore, it is urgent to explore new materials systems with broadband NIR emission.…”
Section: Introductionmentioning
confidence: 99%